2007
DOI: 10.1111/j.1478-3231.2007.01511.x
|View full text |Cite
|
Sign up to set email alerts
|

Nodular regenerative hyperplasia: a deleterious consequence of chemotherapy for colorectal liver metastases?

Abstract: Physicians should be aware of the potential occurrence and therapeutic impact of NRH in patients suffering from CRLM and treated by neoadjuvant 5FU-oxaliplatin-based chemotherapy before major liver surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 25 publications
3
37
0
1
Order By: Relevance
“…In our two patients to these consideration the multinodular pattern has further biased the diagnostic conclusion. Indeed, only Hubert et al [11] previously reported two cases of multiple FNHs occurred in similar circumstances while other authors described patients with single lesions [5,6,9] . Our experience is conveying a further peculiarity, which could be useful for further discussion and experiences in this sense.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our two patients to these consideration the multinodular pattern has further biased the diagnostic conclusion. Indeed, only Hubert et al [11] previously reported two cases of multiple FNHs occurred in similar circumstances while other authors described patients with single lesions [5,6,9] . Our experience is conveying a further peculiarity, which could be useful for further discussion and experiences in this sense.…”
Section: Discussionmentioning
confidence: 99%
“…The natural history of FNH remains unknown, too. Few spontaneous regressions after the suspension of the chemotherapy have been reported as well as some protective effects of bevacizumab on the development of this toxicity [5,11,12] . From the clinical standpoint their proper diagnosis is a delicate matter, since they occur in oncological patients with generally well-documented, and extensive negative At microscopy the lesions were characterized by several fibrous septa highlighted by special stains (Masson staining), and they showed a typical patter at glutamine synthetase immunostaining; D: At higher magnification they contained several dystrophic vessels.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, since our initial report (1), several groups have confirmed the existence of oxaliplatin-related SOS in 25% to 36% of treated patients. This has led to concerns that oxaliplatin-associated hepatotoxicity may decrease the chances of curative liver surgery by increasing morbidity through preoperative hemorrhage, postoperative liver failure, delayed regeneration, and portal hypertension (4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Rare fatal cases have been reported, inducing a group of experts to publish a cautionary note on the use of chemotherapy before surgical liver resection (14).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that the formation of marked nodular hyperplasia may induce portal hypertension [41,42] . In addition, Hubert et al [43] reported that 5-FU-oxaliplatin-based chemotherapy had the potential to induce nodular hyperplasia in patients suffering from colorectal liver metastases. In this study, the portal pressure of the rats in the AEE788-treated group remained within the normal range.…”
Section: Nrh Nrhmentioning
confidence: 99%